Two-Year Institutional Adoption of the EnglishScore App and Its Effects on EFL Proficiency and Engagement - Rizky Eka Prasetya; Adnan Mayof; Achmad Syarif (FKIP Universitas Lampung, 2026)
This study investigates the relationship between the two-year institutional adoption of the EnglishScore mobile assessment application and changes in proficiency and engagement among English as a Foreign Language (EFL) learners at Universitas Budi Luhur. It also explores learners' and instructors' perceptions of the app's integration into the EFL curriculum. A mixed-methods research design was employed. Quantitative data were collected from 120 EFL students through EnglishScore pre- and post-test results and a learner engagement questionnaire. Qualitative data were gathered through semi-structured interviews with 10 students and five instructors, as well as two focus group discussions. Quantitative data were analyzed using paired-samples t-tests and Pearson correlation analysis, while qualitative data were examined through thematic analysis. The results indicated statistically significant differences between pre-test and post-test proficiency scores in grammar, vocabulary, reading, and listening. Engagement levels were generally high, and a moderate-to-strong positive correlation (r = 0.580, p < .001) was found between engagement scores and proficiency gains. Qualitative findings suggested that learners perceived increased motivation, autonomy, and enjoyment when using the app. Instructors reported that the app was useful for diagnostic purposes, although limitations such as the absence of speaking and writing components and occasional technical issues were noted. The findings demonstrate a positive association between sustained use of the EnglishScore app, learner engagement, and observed proficiency gains over the two years. While the results suggest that the app may support language development, further research incorporating control groups or experimental designs is needed to establish causal relationships. Keywords: mobile-assisted language learning, englishscore App, EFL proficiency, learner engagement, institutional integration.